Nominations of the plant world lingocultural aspect - Aizhan Shormakova3Arailym Shormakova1, Lira Ibraymova2,; Laura Daurenbekova5Botakoz Nurzhanova4, (Opción, 2019)
The article investigates the peculiarities of research in the linguistic and cultural aspect of the flora of the Kazakh language and the conceptual sphere of vegetation, the cognitive level of the plant «Zhusan» in the Kazakh language via comparative qualitative research methods. As a result, the wormwood is a phytonem that have reached the conceptual level. In conclusion, each language is a symbolic system that preserves national culture, its culture, its cognitive and taste, its character and its consciousness, its trades and traditions, its traditions and wisdom. Therefore, it is most important to study it in cognitive linguistics.